Cross-National Variation in Aggregate Levels of Life Satisfaction of Gay Men - Morris, Hannah (East Carolina University, 2021)
This project examined the cross-national variation in aggregate levels of life satisfaction of gay men. Using data from the Gay Happiness Index, the World Values Survey, the European Values Study, the International Lesbian, Gay, Trans, and Intersex Association (ILGA), and other secondary sources, I analyzed the determinants of life satisfaction for gay men in 76 countries. Aggregate levels of life satisfaction for gay men were expected to be influenced by the same determinants of life satisfaction for the general population, which included cultural factors such as a country's dominant religion, level of religiosity, and gender equality and socio-political factors such as a country's level of democracy and economic development, as supported by existing literature. Factors unique to the population, however, could also influence aggregate levels of life satisfaction of gay men. Specifically, I expected aggregate levels of public opinion toward gay men and country-level legislation dealing with the criminalization, recognition, and protection of sexual minority populations to significantly influence national-levels of life satisfaction among gay men. Several ordinary least squares (OLS) regression models were used to analyze the data. Aggregate levels of life satisfaction for the general population, as ascertained by the World Values Survey and the European Values Study, were used to better understand what factors may be unique determinants of the life satisfaction of gay men. This study took something traditionally viewed with a microsociological lens and brought it to the macrosociological stage by analyzing cross-national variation in aggregate levels of life satisfaction within the cultural and socio-political context. The results of this study helped to identify the factors that influence life satisfaction for sexual minority groups, and they should prove useful for policy makers who aim to increase country level life satisfaction and increase the life quality of sexual minority populations.
Keywords: Life Satisfaction; Gay Happiness; Gay men; Happiness; Health promotion